Diferensiasi Fatwa Hukum Makanan dan Minuman Beralkohol di Indonesia dan Malaysia Perspektif Hukum Islam - Muhammad Fauzy Basri (Al Muhkam: Journal of Islamic Law and Jurisprudence, 2025)
This study aimed to examined to determine the differences between the MUI and JAKIM fatwas regarding food and beverages containing alcohol and the law on consuming these products based on the Indonesia Ulema Council (Majelis Ulama Indonesia) and Jabatan Kemajuan Islam Malaysia (JAKIM) fatwas. This study uses a qualitative method with a literature study approach. Data were obtained from relevant journals, books, fatwas, and news. Data analysis was carried out through reduction, presentation, and verification of sources, with data validity guaranteed through member checks and source triangulation. The results of the study indicate that the MUI and Jakim Malaysia fatwas differ in handling the issue of alcohol and the law on consuming alcoholic products varies depending on the context and interpretation of each fatwa; This study is expected to provide a more comprehensive understanding for the public regarding this issue.